Proses Komunikasi Terapeutik Dalam Upaya Penyembuhan Pasien Gangguan Jiwa : di Yayasan Al Fajar Berseri - Lia Nanda Wijaya; Maya May Syarah; Ade Budi Santoso (Prisani Cendekia Institute, 2023)
Communication is very important in all forms of individual activity, especially in the relationship between mental patients and caregivers. This aims to reveal and explore the process of therapeutic communication in efforts to cure mental disorder patients at the Al-Fajar Berseri Foundation. In the context of mental health, it uses a therapeutic communication interaction approach. Therapeutic communication interactions with mental disorders are ensured in a calm state so that they can develop useful social relationships. This study aims to answer the therapeutic communication process in an effort to cure mental patients at the Al-Fajar Berseri Foundation. In the research and data collection process, researchers used qualitative research methods with observation techniques, in-depth interviews, audio-visual materials and documentation to obtain information about the therapeutic communication process in efforts to cure mental disorder patients at the Al-Fajar Berseri Foundation which was explained descriptively. The results of research at the Al-Fajar Berseri Foundation show the success of therapeutic communication between mental patients and nurses. This communication process allows mental patients to share stories, get life motivational support and feel valued. The strategy used by the nurse is in the form of verbal communication (such as touch, motivational support and attentive listening). Apart from that, nurses have important stages in therapeutic communication between mental disorders patients and nurses, namely basic communication, an empathetic approach, understanding problems and providing relevant responses to overcome problems faced by mental disorders patients.